2015
DOI: 10.1002/jbmr.2545
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Gamma, but not Calcitriol Improves the Osteopetrotic Phenotypes in ADO2 Mice

Abstract: ADO2 is a heritable osteosclerotic disorder that usually results from heterozygous missense dominant negative mutations in the chloride channel 7 gene (CLCN7). ADO2 is characterized by a wide range of features and severity, including multiple fractures, impaired vision due to secondary bony overgrowth and/or the lack of the optical canal enlargement with growth, and osteonecrosis/ osteomyelitis. The disease is presently incurable, although anecdotal evidence suggests that calcitriol and interferon gamma-1b (IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 26 publications
(39 reference statements)
3
26
0
Order By: Relevance
“…It has previously been reported that IFN-G therapy benefitted some patients with autosomal recessive forms of osteopetrosis [13] as well as the Clcn7 G213R/+ mouse model of Albers-Schönberg disease [14]. IFN-G is only FDA approved for the treatment of autosomal recessive malignant osteopetrosis, but it may be used “off-label” in patients with Albers-Schönberg disease.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has previously been reported that IFN-G therapy benefitted some patients with autosomal recessive forms of osteopetrosis [13] as well as the Clcn7 G213R/+ mouse model of Albers-Schönberg disease [14]. IFN-G is only FDA approved for the treatment of autosomal recessive malignant osteopetrosis, but it may be used “off-label” in patients with Albers-Schönberg disease.…”
Section: Resultsmentioning
confidence: 99%
“…IFN-G is only FDA approved for the treatment of autosomal recessive malignant osteopetrosis, but it may be used “off-label” in patients with Albers-Schönberg disease. Therefore, we treated Clcn7 F318L/+ mice from 4 to 12 weeks of age, using an agent and dosing schedule that improved skeletal properties and markers of bone turnover in Clcn7 G213R/+ mice [14]. We confirmed the bioavailability of IFN-G by measuring serum levels 2 hours after subcutaneous injection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent mouse model of autosomal dominant heterozygous osteopetrosis, substantial improvements in osteopetrotic phenotypes were shown with all doses of interferon c-1b; in contrast, calcitriol (at any dose) did not improve osteopetrotic phenotypes, and high doses were associated with additional increases in bone mass [31].…”
Section: Paucity Of Clinical Trial Data Especially In Patients With mentioning
confidence: 89%
“…1 Most commonly reported treatment-emergent adverse events in a randomized, double-blind trial of subcutaneous interferon c-1b three times weekly (n = 63) vs. placebo (n = 65) in patients with chronic granulomatous disease [24]. *p = 0.01, **p = 0.001. h indicates zero dominant osteopetrosis in which substantial improvements in osteopetrotic phenotypes were shown with interferon c1b, but not with calcitriol [31]. Although calcitriol (generally in combination with a low calcium diet) has been shown to indirectly stimulate bone resorption in some patients with osteopetrosis, it provides little to no benefits with regard to improving the immunological defects associated with the disease [8].…”
Section: Patients (%)mentioning
confidence: 99%